Social audit as an essential control lever for human resources management: Literature review - MHENNA, Rachid (Revue du contrôle, de la comptabilité et de l’audit, 2023)
In a socio-economic context characterized by the liberalization of international trade, increasingly fierce competition, globalized and highly competitive markets, human resources management has become the key success factor for any organization. This is why it is increasingly necessary to have motivated employees with the skills to cope with this new context, but also to ensure the survival of the organization in an ever-changing global arena. In such a context, the company is invited not only to manage its human resources efficiently, but also to control them for the proper functioning of all HR processes in order to improve its performance. Therefore, there are three essential instruments or tools used together, namely The social balance sheet, the HR information system (HRIS) and the social audit. Our article will only focus on the social audit and will give a global theoretical vision on it as a major lever of human resources management control through its important roles and processes.